Can PhET simulate basic electronics circuits for undergraduate students? - Syifaul Fuada; Muhamad Dzikri Danuarteu; Sarah Agustin; Anindya Afina Carmelya; Iffah Fadhilah; Yee Mei Heong; Adisorn Kaewpukdee (JURNAL INFOTEL, 2023)
PhET is one of the most powerful and impressive simulator innovations, widely used in the STEM-based learning process. Based on literature reviews, students are allowed to independently practice their skills and understanding of the material concept using this tool. PheT involves students in process competencies comprehensively and also provides a highly interactive virtual environment for STEM materials, including basic electronics, a sub-category of physics. This tool can also be easily accessed online at https://phet.colorado.edu/ or offline with a note that the user should download and install the application on a PC. An interesting question regarding this education tool is, "can PhET support basic electronics learning in Higher Education (HE)?" Numerous preliminary studies have not answered this question, which is associated with the technical aspect of the tool, because they only focused on the pedagogical aspect. Therefore, this research aims to fill this gap by exploring the capability of PhET in simulating basic electronic circuits that were commonly studied by students in HE, including Kirchoff Current Law (Kirchoof I), Kirchoff Voltage Law (Kirchoff II), Voltage Divider, Series/Parallel Resistors, Wheatstone Bridge, and Star – Delta Resistors. These circuits are simulated in two PhET products, namely, online (1.2.7) and offline (3.20) versions, with numerous setups used to compare their performances to the theoretical calculations. Finally, the answers were obtained clearly from the experimental results in the simulation environment.